2005
DOI: 10.1002/humu.9331
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen novel mutations in theNR0B1(DAX1) gene as cause of adrenal hypoplasia congenita

Abstract: X-linked adrenal hypoplasia congenita (AHC) is a rare developmental disorder associated with primary adrenal insufficiency and combined primary and secondary male hypogonadism. It is caused by deletions or mutations of the NR0B1 (DAX1) gene encoding DAX1, an atypical orphan member of the nuclear receptor superfamily. The continuous molecular genetic analysis of male patients with primary adrenal insufficiency revealed 13 novel mutations within the coding region of the NR0B1 gene which are predicted to inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…1) (Reutens et al, 1999, Lin et al, 2006, Achermann et al, 2000, Muscatelli et al, 1994, Zanaria et al, 1994, Guo, Mason, Stone et al, 1995, Takahashi, Shoji, Haraguchi et al, 1997, Meloni, Cao and Rosatelli, 1996, Nakae, Abe, Tajima et al, 1997, Schwartz, Blichfeldt and Muller, 1997, Peter, Viemann, Partsch et al, 1998, Seminara, Achermann, Genel et al, 1999, Bassett, O’Halloran, Williams et al, 1999, Caron, Imbeaud, Bennet et al, 1999, Merke, Tajima, Baron et al, 1999, Tabarin, Achermann, Recan et al, 2000, Domenice, Latronico, Brito et al, 2001, Wiltshire, Couper, Rodda et al, 2001, Sekiguchi, Hara, Matsuoka et al, 2007, Bernard, Ludbrook, Queipo et al, 2006, Verrijn Stuart, Ozisik, de Vroede et al, 2007, Landau, Hanukoglu, Sack et al, 2010, Li, Liu, Zhang et al, 2010, Sykiotis, Hoang, Avbelj et al, 2010, Abe, Nakae, Yasoshima et al, 1999, Achermann, Meeks and Jameson, 2001, Ahmad, Paterson, Lin et al, 2007, Argente, Ozisik, Pozo et al, 2003, Balsamo, Antelli, Baldazzi et al, 2005, Brown, Scobie, Townsend et al, 2003, Calliari, Longui, Rocha et al, 2007, Frapsauce, Ravel, Legendre et al, 2011, Garcia-Malpartida, Gomez-Balaguer, Sola-Izquierdo et al, 2009, Guo, Burris, Zhang et al, 1996, Habiby, Boepple, Nachtigall et al, 1996, Hamaguchi, Arikawa, Yasunaga et al, 1998, Kinoshita, Yoshimoto, Motomura et al, 1997, Krone, Riepe, Dorr et al, 2005, Lam, Cheng, Poon et al, 2006, Mantovani, Ozisik, Achermann et al, 2002, Mericq, Ciaccio, Marino et al, 2007, Nakae, Tajima, Kusuda et al, 1996, Ozisik, Mantovani, Achermann et al, 2003, Salvi, Gomez, Fiaux et al, 2002, Tsai and Tung, 2005, Wang, Killinger and Hegele, 1999, Wu, Zhang, Zhou et al, 2011, Yanase, Takayanagi, Oba et al, 1996, Zhang, Guo, Wagner et al, 1998, Zhang, Huang, Anyane-Yeboa et al, 2001, Franzese, Brunetti-Pierri, Spagnuolo et al, 2005, Laissue, Copelli, Bergada et al, 2006, Okuhara, Abe, Kondo et al, 2008). After other known causes (i.e., congenital adrenal hyperplasia, CAH) have been excluded, it is estimated that as many as 50% of boys with idiopathic primary adrenal insufficiency may have mutations in DAX1 (…”
Section: Human Studiesmentioning
confidence: 99%
“…1) (Reutens et al, 1999, Lin et al, 2006, Achermann et al, 2000, Muscatelli et al, 1994, Zanaria et al, 1994, Guo, Mason, Stone et al, 1995, Takahashi, Shoji, Haraguchi et al, 1997, Meloni, Cao and Rosatelli, 1996, Nakae, Abe, Tajima et al, 1997, Schwartz, Blichfeldt and Muller, 1997, Peter, Viemann, Partsch et al, 1998, Seminara, Achermann, Genel et al, 1999, Bassett, O’Halloran, Williams et al, 1999, Caron, Imbeaud, Bennet et al, 1999, Merke, Tajima, Baron et al, 1999, Tabarin, Achermann, Recan et al, 2000, Domenice, Latronico, Brito et al, 2001, Wiltshire, Couper, Rodda et al, 2001, Sekiguchi, Hara, Matsuoka et al, 2007, Bernard, Ludbrook, Queipo et al, 2006, Verrijn Stuart, Ozisik, de Vroede et al, 2007, Landau, Hanukoglu, Sack et al, 2010, Li, Liu, Zhang et al, 2010, Sykiotis, Hoang, Avbelj et al, 2010, Abe, Nakae, Yasoshima et al, 1999, Achermann, Meeks and Jameson, 2001, Ahmad, Paterson, Lin et al, 2007, Argente, Ozisik, Pozo et al, 2003, Balsamo, Antelli, Baldazzi et al, 2005, Brown, Scobie, Townsend et al, 2003, Calliari, Longui, Rocha et al, 2007, Frapsauce, Ravel, Legendre et al, 2011, Garcia-Malpartida, Gomez-Balaguer, Sola-Izquierdo et al, 2009, Guo, Burris, Zhang et al, 1996, Habiby, Boepple, Nachtigall et al, 1996, Hamaguchi, Arikawa, Yasunaga et al, 1998, Kinoshita, Yoshimoto, Motomura et al, 1997, Krone, Riepe, Dorr et al, 2005, Lam, Cheng, Poon et al, 2006, Mantovani, Ozisik, Achermann et al, 2002, Mericq, Ciaccio, Marino et al, 2007, Nakae, Tajima, Kusuda et al, 1996, Ozisik, Mantovani, Achermann et al, 2003, Salvi, Gomez, Fiaux et al, 2002, Tsai and Tung, 2005, Wang, Killinger and Hegele, 1999, Wu, Zhang, Zhou et al, 2011, Yanase, Takayanagi, Oba et al, 1996, Zhang, Guo, Wagner et al, 1998, Zhang, Huang, Anyane-Yeboa et al, 2001, Franzese, Brunetti-Pierri, Spagnuolo et al, 2005, Laissue, Copelli, Bergada et al, 2006, Okuhara, Abe, Kondo et al, 2008). After other known causes (i.e., congenital adrenal hyperplasia, CAH) have been excluded, it is estimated that as many as 50% of boys with idiopathic primary adrenal insufficiency may have mutations in DAX1 (…”
Section: Human Studiesmentioning
confidence: 99%
“…As reported, there were a few mutations in the amino-terminal domain (7,8,10). Verrijn Stuart et al reported an amino-terminal DAX1 missense mutation (W105C) associated with isolated mineralocorticoid deficiency, and further structure-function studies suggested that the W105C and other mutations in the amino terminus were compensated by the presence of repeated LXXLL motifs that mediated DAX1 interactions with other protein (8).…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, the detected mutation has not been reported previously. It leads to a frame-shift, a premature stop codon at p.389 in the central region of the LBD of the DAX1 protein and results in a truncated DAX1 protein with disrupted carboxy-terminus thus preventing the expression of a functional DAX1 protein (10). We reviewed the mutations in the DAX1 gene in Chinese patients with AHC through PubMed and the power database research centers of China (CQVIP, WANGFA DATA and CNKI).…”
Section: Discussionmentioning
confidence: 99%
“…Other mutations in the same position with substitution by a different amino acid were described in two siblings (Trp291Cys; Trp291Stop) with hyperpigmentation as the only initial manifestation, who later developed adrenal insufficiency at the ages of 2 and 3 [10], and in a patient with clinical features and hormonal pattern of adrenal insufficiency diagnosed at the age of two weeks [6], compared with that of our patient (Trp291Arg), which underlines the importance of Trp at position 291 for the functional role of DAX1 in the hypothalamo-pituitary-gonadal axis. In fact, the PolyPhen and SIFT software predicted that the substitution of tryptophan by arginine would not be tolerated, as it might be damaging.…”
Section: Discussionmentioning
confidence: 96%